Improved design of passive damping for single phase grid‐connected LCL filtered inverter considering impedance stability - Ramy Ali; Hamed Heydari‐doostabad; Shahab Sajedi; Terence O'Donnell (IET Power Electronics, 2024)
Abstract Grid‐connected inverters with an inductor–capacitor–inductor (LCL) filter usually require the implementation of damping in the filter to suppress the resonance associated with the filter and hence ensure internal stability. The value for the damping resistor is commonly chosen as one‐third of the capacitive reactance at the resonance frequency of the LCL filter. However, this commonly‐used principle does not take into account the external stability of the inverter, i.e. the potential for an interaction between the inverter output impedance and the grid impedance. This work discusses a new design for the damping resistor to assure the external stability of the voltage source inverter as well as its internal stability. The analysis shows that the proposed design can ensure the external stability of the voltage source inverter with different grid impedances as well as robustness against the variations of the filter parameters while maintaining low power losses and an acceptable attenuation rate for high‐frequency harmonics. To validate the theoretical analysis, a 1 kW, 110 V laboratory prototype is implemented. The obtained results confirm the applicability of the proposed design approach.